Respostas
respondido por:
2
Olá!
![4x + 2x + 4 + 3 - 5x - 6 = 4x + 2x + 4 + 3 - 5x - 6 =](https://tex.z-dn.net/?f=4x+%2B+2x+%2B+4+%2B+3+-+5x+-+6+%3D+)
Coloque os termos similares em evidência e some os demais:
![x + 1 x + 1](https://tex.z-dn.net/?f=x+%2B+1)
ESPERO TER AJUDADO!!
Boa tarde e bons estudos!
Coloque os termos similares em evidência e some os demais:
ESPERO TER AJUDADO!!
Boa tarde e bons estudos!
diego80667:
obg
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás